2007
DOI: 10.1504/ijesd.2007.012739
|View full text |Cite
|
Sign up to set email alerts
|

Corporate environmental and financial performances and the effects of information-based instruments of environmental policy in Japan

Abstract: Focusing on 278 listed corporations in Japan, the present study tests the hypothesis that robust environmental conservation activities have a positive effect on their financial performance. It also examines the role played by the environmental policies introduced and strengthened by the government since the end of the 1990s. By a statistical causality analysis using data from 1999 to 2003 we have shown that a positive effect of corporate environmental activities on financial performance was verified more clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…By examining 278 listed companies in Japan from 1999 to 2003, the study reveals that there is a positive effect of corporate environmental activities (using Nikkei Environmental Management Score Report) on financial performance (Tobin's 1 q minus 1 and ROA). The study therefore, suggests further examination is needed (Nakao et al 2005). Interestingly, the positive relationship earlier established in the energy-intensive industry group turns negative as a result of the recent trend of tightening climate policies.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…By examining 278 listed companies in Japan from 1999 to 2003, the study reveals that there is a positive effect of corporate environmental activities (using Nikkei Environmental Management Score Report) on financial performance (Tobin's 1 q minus 1 and ROA). The study therefore, suggests further examination is needed (Nakao et al 2005). Interestingly, the positive relationship earlier established in the energy-intensive industry group turns negative as a result of the recent trend of tightening climate policies.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Nakao et al (2005) first proposed environmental accounting as a tool for promoting environmental innovations. CSP has been operationalized in literature as including charitable contributions and philanthropy, environmental management, performance, sustainability and until recently, environmental innovations.…”
Section: Discussionmentioning
confidence: 99%
“…This condition encourages firms to amend their business practice more friendly with the environment. The relationship between environment and business practice has been popular area in the research world and the effect of environment on business performance is found scholars [14], [15] [16][17] [18]. Firms understanding the externality would seek the idea to prevent environmental pollution, even with the release of the eco-production technology.…”
Section: Csr For Environmentmentioning
confidence: 99%
“…Other scholars suggest that good environmental performance has a positive influence on financial performance (Freedman and Patten, 2004;Griffin and Sun, 2013). For example, Murphy (2002) and Nakao et al (2007b) investigated the relationship between CSR in the environmental dimension and financial performance and found a positive relationship between the two variables. King et al (2002) argue that when firms engage in and disclose environmental protection activities, they send positive signals that create a good corporate image, improves product sales, and in turn improves the financial performance of the firm.…”
Section: Csrd In the Environmental Dimensionmentioning
confidence: 99%